KONSEP KEPEMIMPINAN SOEHARTO DALAM BUTIR-BUTIR BUDAYA JAWA - Wachid Eko Purwanto (Universitas Ahmad Dahlan, 2017)
This study aimed to describe (1) the concept of leadership in pituduh that fit into the category ketuhunan and (2) the concept of leadership in wewaler (Prohibition). This research is the study of literature. The method used in this study is a content analysis method. The object of this study is the concept of Suharto. The subjects were Unen-Unen (proverb). Data collected with a note reading techniques. The primary data source is selected by using purposive sampling method. The conclusions made by the formulation and the conclusion of the data that has been analyzed and interpreted with the use of the theory of Paul Ricoeur hermeneutics. The results of this study are as follows. First, the concept of leadership in pituduh (hint) that fit into the category of divinity has two leadership instructions: (1) be applicable authorities properly, (2) the truth of God into a basic truth of the ruler. The concept of leadership in pituduh (hint) that fit into the category of nationality include (1) a good leader is a dreamer fair, spirited noble, able to give jobs to the people, (2) A good leader is a leader who can reassure the people, (3 ) A good leader is willing and able to fix the flaws and vices, (4) leadership is a trust from God, (5) A good leader wary of praise, (6) a good leader wary of bad temper, (7) the leader of the evil is the leader dangerous, (8) Choosing a good leader is not an evil leader, (9) the evil leader will declare evil is goodness. Second, the concept of leadership in wewaler (Prohibition) includes two categories, namely humanity and nationality. Category prohibition in humanitarian terms include a ban on the leaders of banned arrogant leader. The prohibition in respect of nationality shows that good leaders leaned pleasure and sadness on the basis pleasure and pain the people, not on personal pleasure and pain.